MEMAHAMI CARA KERJA PRAGMATISME DALAM PENDIDIKAN: REFLEKSI KRITIS ATAS FILM LASKAR PELANGI - Moch Najib Yuliantoro (Jurnal Filsafat "WISDOM", 2017)
This paper aims to understand the Pragmatism way of thinking in the practice of education. As a case study, Riri Reza's Laskar Pelangi is used to find out how Pragmatism practices in education in Indonesia. By using descriptive-critical method of interpretation and interpretation, it is revealed that the main characters in the film Laskar Pelangi experience a dilemma situation that leads them to choose a way of life based on internal logic and actual experience. As for the criticisms, as well as the implications of, pragmatism thinking refers its potentiality to the individualistic way of thinking, especially in the axiological sphere, namely by believing that there is no universal value in social life.